WAYS OF MODERNIZATION AND IMPROVEMENT OF ARCHITECTURAL EDUCATION IN UKRAINE - Kateryna Kapushchak; Nina Hnes; Yuliya Idak (International Journal of Innovative Technologies in Social Science, 2021)
The article identifies the problems faced by the Ukrainian architectural education and formulates the ways to overcome it. To formulate them, a survey was conducted among students studying abroad through the prism of comparing methodological approaches to the organization of the educational process and its content. The basic ones are those related to the practical component, technological equipment, the organization of the educational process and the relevance of the knowledge gained.